Effect of Beef Liver Addition on the Physicochemical and Color Characteristics of Chicken Patties - Dedes Amertaningtyas; Kiki Nila Agustin; Jessica Aprillia (Journal of Agriprecision & Social Impact, 2026)
This study aimed to determine the effect of different levels of beef liver addition on the nutritional, physicochemical, and color characteristics of chicken patties. Beef liver, an underutilized animal by-product with high nutritional value, was incorporated at different levels (0%, 20%, 40%, and 60%) into chicken patty formulations. The experiment was conducted using a Completely Randomized Design with four treatments and five replications. The collected data were analyzed using analysis of variance (ANOVA) and followed by Duncan’s Multiple Range Test (DMRT). The results showed that the addition of beef liver had no significant effect (P>0.05) on protein content, water activity (aw), and b* values, but had a highly significant effect (P<0.01) on moisture content, fat content, cooking loss, texture, and color characteristics (L* and a*). Increasing beef liver levels improved the nutritional profile and modified the physical and visual characteristics of the patties. These findings demonstrate the potential of beef liver as a value-added functional ingredient for developing nutritious chicken patties while promoting the sustainable utilization of underutilized livestock by-products.